EVALUATION OF ORAL HEALTH CONDITIONS IN THE ELDERLY AT THE PATOS FIP–PB PHYSICAL THERAPY SCHOOL CLINIC (Fiep Bulletin - online, 2012)
Introduction: With the increase in the proportion of elderly people in Brazil, the occurrence of oral health problems related to caries is also increasing. Researchers affirm that studies that contribute to the verification of the use of indices and indicators of oral health should be performed, especially in the elderly population. Objective: To examine the state of oral health in an elderly group at the Physiotherapy Clinic of the Integrated College of Patos. Methodology: A descriptive study with a quantitative approach, performed with 40 subjects in the Physiotherapy Clinic of the Integrated College of Patos, PB. Data were collected during the month of May 2010 through a structured interview. Data were analyzed descriptively and presented as a table. The research follows the guidelines of the CNS/MS Resolution 196/96. Results: regarding the hygiene of the oral cavity, 100% of the sample responded to perform oral hygiene. However, 57.5% (23) said they no longer have any teeth in the mouth, and 12.5% ??(5) reported missing an average of 24 teeth. Of these, 53.32% (8) responded still having at least four restored teeth in their mouth. Around 67.5% (27) of respondents said they are not happy with the current conditions of their oral health, however 87.5% (35) said they can feed themselves without any problems and 95% (38) reported never having felt inferior because of the condition of their oral health. Regarding dentist visits, 80% (32) of the respondents claimed not to be going to the dentist often, but 95% (38) had received guidance on how to sanitize and how to take better care of their teeth. Conclusion: the oral health conditions of the elderly people represented in this study are not satisfactory and reflects the need to develop programs to promote health and rehabilitation services for this population.
Keywords: Elderly; Oral health; Prevention